2020
DOI: 10.1021/acs.jpca.0c04707
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Struvite. Elucidating Structure of Infrared Spectrum in High Frequency Range

Abstract: Study of structure and optical properties of magnesium ammonium phosphate hexahydrate crystal known as struvite is presented. Experimentally determined infrared (IR) and ultraviolet–visible (UV–vis) spectra are compared with the theoretical predictions of density functional methods. Examination of the interatomic bond lengths, Mulliken atomic charges, and binding energies of water in the magnesium hexahydrate cation, together with the analysis of the hydrogen bond pattern have allowed us to explain a special f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…We confirm that M05-2X is particularly well suited to study struvite, as already reported in Ref. [4]. The knowledge of mechanical properties of struvite may point the manner by which urinary stones interact with the mechanical stresses produced by extracorporeal shock-wave lithotripsy -one of the most frequently used procedures for treatment the urinary stones.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We confirm that M05-2X is particularly well suited to study struvite, as already reported in Ref. [4]. The knowledge of mechanical properties of struvite may point the manner by which urinary stones interact with the mechanical stresses produced by extracorporeal shock-wave lithotripsy -one of the most frequently used procedures for treatment the urinary stones.…”
Section: Discussionsupporting
confidence: 87%
“…Primitive cell of struvite crystal, picture generated using VESTA3 software [3]. The assumed color code: whitehydrogen atoms; redoxygen atoms; bluenitrogen atoms in NH + 4 tetrahedra; orangephosphorus atoms in PO [3][4] tetrahedra; greenmagnesium atoms in Mg(H 2 O) 2+ 6 octahedra.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The symmetric ν 1 phosphate stretch for struvite is located at 943 cm –1 , while the ν 4 mode corresponds to 560 cm –1 . , The hydrogen-bonded hydroxyl/water and ammonium species lead to the increase of a prominent region in struvite, with a broad band centered around 3134 cm –1 and a shoulder around 2950 cm –1 . , The hydroxyl region of HAP does not exhibit similar broad peaks due to the lack of crystal water but the sharp 3575 cm –1 peak corresponds to the OH stretching mode . Struvite contains tetrahedral NH 4 + groups, as evidenced by the 1442 and 1690 cm –1 peaks. , …”
Section: Resultsmentioning
confidence: 99%
“…When MAP is the main component, it is easy to identify as shown in the infrared spectrum of pure struvite in Figure 4. Its main characteristics are a very strong ν 3 PO 3− 4 vibration at 1005 cm −1 with a strong and broad absorp- tion between 3700 and 2100 cm −1 due to ν 3 stretching vibrations of hydrogen peaks of the six water molecules and of the NH4 + group, with a decrease on the right side as a pseudo-plateau between 2500 and 2345 cm −1 [61,62]. Another interesting vibration is the ν 2 bending peak of the ammonium group at 1435 cm −1 .…”
Section: Infrared Spectroscopy Identification Of Map and Wkmentioning
confidence: 99%